Exploring Indonesian senior high school teachers’ perceptions of first language use in teaching English - Nanda, Dodi Widia; Duhn, Iris; Prananda, Gingga; Pebriana, Putri Hana; Andiopenta, Andiopenta; Ridwan, Muannif; Ricky, Zuhar (Intelektual Pustaka Media Utama, 2024)
This study aims to investigate Indonesian senior high school teachers’ perceptions of using the first language (L1) when teaching English because Indonesian teachers tend to have negative perceptions toward the application of the L1, while the L1 is needed in a situation where Indonesian students have limited skills in English. The semi-structured interview was applied to collect data, while thematic analysis was used to analyse it. The result showed that the teachers have three different positions in perceiving the use of the L1: the virtual position, maximal, and optimal positions. Although they have different perceptions toward the application of the L1, a major insight can be concluded about the limited use of the L1 for specific reasons, such as considering teachers’ and students’ English abilities, learners’ needs, and the type and the difficulty of the given task or assignment. The L1 can be functioned as scaffolding in three aspects: when teaching grammar, vocabulary, and when giving instructions. Teachers may consider this study’s results as the information to use the L1 in classrooms. This may also be beneficial for Indonesian educational stakeholders and the government to specifically define what type of scaffolding that teachers can use the L1 to teach English.